Impact of Maternal Anxiety and Stress During Pregnancy on Fetal Neurodevelopment: A Longitudinal Cohort Study in Jakarta, Indonesia - Leonardo Simanjuntak; Tomiola Owkwulu; Tanvir Ahmed; Reza Andrianto; Lestini Wulansari (Scientia Psychiatrica, 2025)
Introduction: Maternal anxiety and stress during pregnancy are increasingly recognized as significant factors influencing fetal neurodevelopment. This study investigated the impact of maternal anxiety and stress levels during pregnancy on various aspects of fetal neurodevelopment in a cohort of pregnant women in Jakarta, Indonesia. Methods: A longitudinal cohort study was conducted at three major hospitals in Jakarta, involving 500 pregnant women in their first trimester. Maternal anxiety and stress levels were assessed using the State-Trait Anxiety Inventory (STAI) and the Perceived Stress Scale (PSS) at three time points: first trimester (10-14 weeks), second trimester (20-24 weeks), and third trimester (30-34 weeks). Fetal neurodevelopment was assessed using fetal movement counting, fetal heart rate variability (using Doppler ultrasound), and later, infant neurodevelopmental assessments at 6 and 12 months postpartum using the Bayley Scales of Infant Development III. Data analysis involved correlation and regression analyses to examine the relationship between maternal anxiety/stress and fetal/infant neurodevelopmental outcomes. Results: The study found a significant positive correlation between maternal anxiety and stress levels across all trimesters. Higher maternal anxiety and stress, particularly in the second and third trimesters, were associated with reduced fetal movement counts (p < 0.05) and altered fetal heart rate variability patterns (p < 0.01). Furthermore, higher maternal anxiety and stress during pregnancy were associated with lower scores on the cognitive and motor scales of the Bayley Scales at both 6 and 12 months (p < 0.001). Specifically, maternal anxiety in the third trimester was the strongest predictor of lower cognitive scores at 12 months. Conclusion: Maternal anxiety and stress during pregnancy, particularly in the second and third trimesters, have a demonstrable impact on fetal neurodevelopment and subsequent infant development. These findings highlight the importance of screening for and managing maternal anxiety and stress during pregnancy to promote optimal fetal and infant neurodevelopment. Interventions targeting stress reduction and anxiety management should be integrated into routine prenatal care.